Wind energy resource over Europe under CMIP6 future climate projections: What changes from CMIP5 to CMIP6. (November 2021) - Carvalho, D.; Rocha, A.; Costoya, X.; deCastro, M.; Gómez-Gesteira, M.
Abstract: The impacts of climate change on the future European wind resource were investigated according to two of the latest future climate scenarios of CMIP6. Towards the end of the current century SSP2-4.5 projects that some small localized areas can experience an increase in the future wind energy resource (around 15–30 % in eastern Ukraine and Turkey). However, all other European areas will experience a significant decrease (5–15 %), particularly towards the end of the current century in the British Isles, Poland, western Ukraine and northern Norway (10–20 %). For the same time period, SSP5-8.5 projects a decrease in future wind energy resource in practically all of Europe (10–20 %), particularly at northern Norway, Poland and western Ukraine (25–30 %). There is significant uncertainty in changes in the wind resource inter- and intra-annual variability, although SSP2-4.5 projects an increase of the latter over Iberia and eastern Ukraine. These results reveal that CMIP6 future wind resource projections for Europe show relevant differences when compared to CMIP5. Unlike CMIP5, CMIP6 does not project an increase in wind resource for Northern Europe, showing a strong decline for practically all of Europe by the end of the century (SSP5-8.5). CMIP6 projects a strong increase in wind resource in future summer in some areas of southern Europe, whereas CMIP5 projected the opposite (decrease in southern Europe during summer). Unlike CMIP5, in CMIP6 stronger radiative forcing scenarios not only enhance the differences when compared to milder scenarios, but also change the spatial patterns of changes in the wind resource. Highlights: Future European wind resource was investigated with CMIP6 future climate projections. SSP5-8.5 projects a decrease in future wind resource for practically all of Europe. However, SSP2-4.5 projects that some areas can witness a slight increase of wind resource. Changes in the wind resource inter- and intra-annual variability show high uncertainty. CMIP6 and CMIP5 future wind resource projections for Europe show relevant differences.